2021
DOI: 10.1186/s12913-020-06055-y
|View full text |Cite
|
Sign up to set email alerts
|

Addressing unmet basic needs for children with sickle cell disease in the United States: clinic and staff perspectives

Abstract: Background The purpose of this study was to assess pediatric hematology clinic staff’s perspectives regarding barriers and facilitators in addressing unmet basic needs for children with sickle cell disease (SCD). Methodology Six focus groups were held at four urban pediatric hematology clinics in the Northeastern region of the United States from November to December 2019. Discussion questions were developed to align with the integrated Promoting Ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…A call for better connection between SCD clinical and social services beyond clinical care included consideration for SES factors in strategies to improve overall health of people with SCD 50 . A holistic approach to care, including routine screening for and intervention for SDoH, is consistent with a recent national report recommending that health care systems implement better integration of patients’ social needs into health care delivery, especially where low SES is prevalent 51–53 …”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…A call for better connection between SCD clinical and social services beyond clinical care included consideration for SES factors in strategies to improve overall health of people with SCD 50 . A holistic approach to care, including routine screening for and intervention for SDoH, is consistent with a recent national report recommending that health care systems implement better integration of patients’ social needs into health care delivery, especially where low SES is prevalent 51–53 …”
Section: Discussionsupporting
confidence: 76%
“…50 A holistic approach to care, including routine screening for and intervention for SDoH, is consistent with a recent national report recommending that health care systems implement better integration of patients' social needs into health care delivery, especially where low SES is prevalent. [51][52][53] Study limitations include a single-site, clinic-based convenience sample of modest size with possible selection bias for those who attended their child's scheduled hematology visit during our sampling However, food insecurity reports between parents and children may be discordant. 44,55,56 Children may also be more aware of their caregivers' struggles with meeting the family's food needs, and thus add to their stresses.…”
Section: Discussionmentioning
confidence: 99%
“…28 Additionally, children with SCD have higher healthcare usage than other low-income children due to the need to seek care for multiple conditions related to their SCD, 12 and also experience more healthcare barriers. 29 Therefore, household SES (ie, parental education), 30–33 can directly affect the frequency of healthcare usage, matching our analyses’ trends. Although, visiting ER/urgent care frequently is often necessary for individuals living with SCD due to the nature of the condition and irrespective of their SES, 14 25 existing studies have indicated that patients are hesitant to visit the ER/urgent care due to previous negative healthcare experiences and stigmatisation 14 15 34 because of providers’ implicit biases.…”
Section: Discussionmentioning
confidence: 54%
“…As the current literature suggests, children with SCD typically come from families of a lower SES12 and therefore, experience significant social challenges when managing their condition, often waiting too long to seek care 28. Additionally, children with SCD have higher healthcare usage than other low-income children due to the need to seek care for multiple conditions related to their SCD,12 and also experience more healthcare barriers 29. Therefore, household SES (ie, parental education),30–33 can directly affect the frequency of healthcare usage, matching our analyses’ trends.…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies of SDOH integration in specialty care are mostly focused in children. [28][29][30] However, as our case demonstrates, it is equally important for SDOH to be addressed in adults in the specialty care setting.…”
Section: Table I Resources To Help Address Sdohmentioning
confidence: 88%